The Impact of Employee Engagement and Organizational Culture on Employee Performance Mediated by Job Satisfaction: Evidence from Bhayangkara Hospital Surabaya - Rousita, Nor Handiah; Sundjoto, Sundjoto; Rahayu, Sri; Fitrianty, Rifda (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The performance of hospital employees plays a pivotal role in ensuring efficient service delivery, patient satisfaction, and overall organizational effectiveness. Bhayangkara Hospital Surabaya requires a workforce that is engaged, culturally aligned, and satisfied with their roles to achieve high performance standards. This study examines the effects of employee engagement and organizational culture on performance outcomes, incorporating job satisfaction as a mediating variable. Using a quantitative explanatory design, 70 respondents were randomly selected from a population of 234 non-medical staff, ensuring proportional representation across different hospital units. Data were collected using validated Likert-scale instruments and analyzed through multiple linear regression and path analysis. Findings show that both engagement and organizational culture significantly enhance job satisfaction, explaining 59.9% of its variance. Additionally, engagement and culture directly impact employee performance, accounting for 47.6% of variation, while job satisfaction strongly mediates performance outcomes, explaining 64.1% of its variability. These results emphasize that a combination of strong engagement, supportive organizational culture, and high job satisfaction fosters superior productivity, motivation, and work quality among hospital staff. The study offers practical guidance for hospital management, highlighting the importance of creating work environments that encourage employee involvement, uphold shared cultural values, and nurture satisfaction to improve overall performance. Further research is recommended to explore other influential factors, including leadership style, emotional intelligence, and workplace climate, to develop comprehensive strategies for enhancing employee effectiveness in healthcare organizations.